Brain Signal Analysis Using Different Types of Music - Mohd Nasir, Siti Ayuni; Wan Mahmud, Wan Mahani Hafizah (International Journal of Integrated Engineering, 2015)
Music is able to improve certain functions of human body physiologically and psychologically. Music also can improve attention, memory, and even mental math ability by listening to the music before performing any task. The purpose of this study is to study the relation between types of music and brainwaves signal that is differences in state of relaxation and attention states. The Electroencephalography (EEG) signal was recorded using PowerLab, Dual Bio Amp and computer to observes and records the subject brain activity in three condition; before, during, and after listening to different types of music; Light, Rock, Mozart, Al-Quran recitation and Jazz. The brainwave reaction of the subjects is compared during these three conditions. The hypothesis of this study is; Beta wave is increased at attention state and decrease at relaxation state. To analyze the data, Labchart7 software was used. The EEG data that has been recorded is processed using Digital Filter and the features of EEG signal is extracted and recorded by Data Pad that included in Labchart7 software. Then, the data is analyzed from mean of group features and also the average amplitude of Alpha and Beta wave. The results from this study are; the attention state of students is increased (Beta increased) while listening to Rock, AlQuran recitation and Mozart music when compared between during and before condition. Meanwhile, Beta wave is decreased while listening to Light and Jazz music thus showing the decrements of student’s state attention. Therefore, the result obtained may help students to choose better type of music or similar to help increases their concentration and focus while study.